2008
DOI: 10.1038/sj.bmt.1705957
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of newborn thymus plus hematopoietic stem cells can rescue supralethally irradiated mice

Abstract: We attempted to rescue supralethally irradiated (SLI) mice by transplantation of hematopoietic stem cells (HSCs) plus thymus from variously aged donors (fetus, newborn and adult). Although the transplantations of these kinds of HSCs alone showed a very short survival, newborn liver cells (NLCs) (as the source of HSCs) plus newborn thymus (NT) transplantation markedly improved the survival rate. The transplantation attenuated severe damage in the small intestine, which is one of the major causes of death by SLI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…The combination of BMT and TT is effective in restoring donor-derived T cell function in aged, chimeric-resistant, tumor-bearing, supralethally irradiated, and low-dose irradiated mice and also in mice injected with a small number of BMCs [10][11][12][13]. We have further demonstrated that IBM-BMT þ TT is effective for tumor regression and long-term survival [14,15].…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…The combination of BMT and TT is effective in restoring donor-derived T cell function in aged, chimeric-resistant, tumor-bearing, supralethally irradiated, and low-dose irradiated mice and also in mice injected with a small number of BMCs [10][11][12][13]. We have further demonstrated that IBM-BMT þ TT is effective for tumor regression and long-term survival [14,15].…”
Section: Introductionmentioning
confidence: 75%
“…The proliferative activity of T cells from the fetal and newborn thymus is much higher than in those from adults [16,17], whereas the level of cytokine production increases with age [18]. In this regard, we have recently found that supralethally irradiated mice are rescued by [newborn liver cell transplantation (NLT) þ newborn TT (NTT)] more efficiently than by [BMT þ adult TT (ATT)] or [fetal liver cell transplantation (FLT) þ fetal TT (FTT)] [12]. In the present study, we investigated the most effective donor age for [hematopoietic stem cell transplantation (HSCT) þ TT] for tumor-bearing hosts.…”
Section: Introductionmentioning
confidence: 99%
“…Although the reason for this discrepancy is unclear, we also observed the same in newborn TT with BMT in supralethally irradiated mice. 15 Transplanted thymus may predominantly supply CD4T cells or suppress CD8T cells. The low number of all lymphocyte subsets in the mice treated with IBM-BMT plus DLI may be the result of the GVHD.…”
Section: Discussionmentioning
confidence: 99%
“…12 We have also developed concurrent thymus transplantation (TT) with BMT; BMT plus TT was found to be effective for recipients showing thymic involution caused by aging, supralethal irradiation, chimeric resistance or malignant tumor. [13][14][15][16] However, it is unknown whether BMT plus TT is effective when using a nonmyeloablative regimen and/or when transplanting insufficient numbers of BMCs. In addition, TT has only been clinically applied to patients with DiGeorge syndrome or HIV infection who show hypoplasia of the thymus; 17,18 the effects of TT on BMT have not been extensively examined.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that TT can also significantly increase the percentage of CD4 + T cells (but not CD8 + T cells) compared with BMT alone (27). Because no serious GvHD or thymus impairment was induced by TT, we hypothesized that the derivation of CD4 + T cells could be the key point.…”
Section: Dli-derived Cd4 + T Cells Induce Thymic Impairmentmentioning
confidence: 99%